2020
DOI: 10.4132/jptm.2020.07.18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human papillomavirus (HPV) prediction using the International Endocervical Adenocarcinoma Criteria and Classification system, compared to p16 immunohistochemistry and HPV RNA in-situ hybridization

Abstract: Cervical cancer is the fourth most frequent cancer in woman worldwide, and up to 10%-20% of all cases are adenocarcinomas [1-3]. The classification of endocervical adenocarcinomas (ECA) as per the 2014 World Health Organization (WHO), stratifies ECA into different subtypes based predominantly on morphologic features. However, these categories do not reflect our modern understanding of ECA pathogenesis. Carcinomas of the uterine cervix and multiple other organ sites prone to highrisk human papillomavirus (HPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Cases where neoadjuvant chemoradiation affected proper histologic assessment, repeat cases, and adenosquamous carcinomas were excluded. Slides of all ECAs were reviewed and reclassified as previously established under the IECC criteria, using a combination of histology, p16 immunohistochemistry, and HPV RNA in situ hybridization as previously described (12). In brief, ECAs were assigned as HPVA based on the presence of classic HPVA histomorphologic features including apical mitotic features and apoptotic bodies present at scanning magnification.…”
Section: Case Selection and Tumor Classificationmentioning
confidence: 99%
“…Cases where neoadjuvant chemoradiation affected proper histologic assessment, repeat cases, and adenosquamous carcinomas were excluded. Slides of all ECAs were reviewed and reclassified as previously established under the IECC criteria, using a combination of histology, p16 immunohistochemistry, and HPV RNA in situ hybridization as previously described (12). In brief, ECAs were assigned as HPVA based on the presence of classic HPVA histomorphologic features including apical mitotic features and apoptotic bodies present at scanning magnification.…”
Section: Case Selection and Tumor Classificationmentioning
confidence: 99%
“…32 study, where they also reported a higher interobserver agreement in mesonephric carcinoma and clear cell carcinomas. Ren et al 15 also reported that WHO 2020 can predict the HPV status in most of the cases.…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, M/A criteria and cytoplasmic features were not enough for correct classification in some cases and ancillary tests are needed. Ren et al (15) also reported challenges on their initial histologic assessment of 5 HPVA; mucinous ECAs. They were reclassified as HPVI-gastric type, HPVI-mucinous-NOS, and unclassifiable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate RNA and HPV controls were included. The system contains probes targeting E6 and E7 mRNA for the following 18 high risk types: 16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 68, 73, and 82. ISH stained TMAs were scanned and digitized using Aperio, and the tissue spots were independently reviewed by 3 pathologists who scored HPV RNA-ISH expression as positive per the manufacturers specifications of any nuclear or cytoplasmic signal occurring in a tumor cell.…”
Section: Methodsmentioning
confidence: 99%